QTL for Maize Midparent Heterosis in the Heterotic Pattern American Dent × European Flint under Corn Borer Pressure - Samayoa, Luis F.; Malvar, Rosa A.; Butrón, Ana (Frontiers in Plant Science, 2017)
Despite the importance of heterosis and the efforts to comprehend this phenomenon, its molecular bases are still unknown. In this study, we intended to detect QTL for mid-parent heterosis under infestation with the Mediterranean corn borer (MCB, Sesamia nonagrioides Lef.) using a North Carolina design III approach with a RIL population derived from a European flint inbred (EP42) x American dent inbred (A637) cross. QTL for heterosis of kernel yield have been positioned in regions corresponding to previously identified QTL for the same trait in different backgrounds. These results reinforce the high congruency of genes controlling heterosis across populations, even when populations have been developed from different heterotic patterns. A high percentage of genetic variation for mid-parent heterosis (Z2 transformation) for kernel yield could not be explained. Furthermore, genomic regions involved in heterosis for yield and plant height were not found despite the high genetic correlation between Z2 transformations for kernel yield and plant height. The moderate power in detecting QTL for mid-parent heterosis suggests that many genes with low augmented dominance effects contribute to the genetic architecture of mid-parent heterosis; dominance and additive-additive epistatic effects could contribute to heterosis. However, results from this and previous studies suggest that the region 8.03-8.05 deserves special attention in future works in order to fine map loci involved in mid-parent heterosis for yield.